Первинні та вторинні внутрішньотранспозиційні ознаки орудного відмінка іменників: формально-синтаксичний і комунікативний аспекти (на матеріалі волинських народних пісень) - Костусяк, Наталія Миколаївна; Kostusyak, N. M. (Мистецька агенція “Терен”, 2010)
У статті комплексно досліджено грамему орудного відмінка, інструменталь розглянуто на тлі синтаксичного рівня мови, обґрунтовано його первинні та вторинні формально-синтаксичні й комунікативні ознаки, вказано на внутрішню транспозицію орудного відмінка. The article presents complex study of the instrumental case grammeme. In the article the instrumental case on the base of the syntactical language level is analyzed, its initial and additional forms of the formally-syntactical and communicative characteristics are described, inward transposition of the instrumental case are shown.
Initial and additional intra-transposition pronounced signs of instrumental nouns: formally-syntactical and communicative aspects (Based on folk songs of Volyn)
Keywords: орудний відмінок; інструменталь; транспозиція; керований член речення; тема; рема; an instrumental case; a transposition; a main part of the sentence; a theme; a rhyme; 811.161.2’367.622:81’366.546